IDENTIFIKASI DAYA TARIK SOSIAL MEDIA INFLUENCER TASYA FARASYA - Aiman, Dwi Feni (Jurnal Visi Komunikasi, 2020)
Social media influencer as a strategy that markets products, with a variety of social media platforms such as Instagram, YouTube, Facebook and other social media, social media influencers provide Brands to market and advertise directly to their target audience. There are several influencers that have been categorized according to the skills or concepts they made from the beginning, such as beauty influencers, influencers whose concept of beauty. Through reviews given by social media influencers will add value to the Brand's credibility and increase public awareness of the Brand so that the public can use the value of the service or product offered to a personal level. This study discusses how to increase the appeal possessed by one of the beauty influences, namely Tasya Farasya in supporting a "Safi" skin care product on the YouTube platform. This type of research is constructivism with qualitative research. The method used was survey research on followers of Tasya Farasya. Where researchers collect data at the premiere of transferring questionnaires to respondents and observations on Tasya Farasya's Instagram or YouTube social media accounts. Based on the results of the study, the appeal of social media influencer Tasya Farasya's in the eyes of the public in promoting Safi's products is on the credibility given by Tasya as an honest, detailed and beautiful influencer beauty.